The quality of judicial decisions in cases of bullying in professional educational institutions - O. G. Yushkevych (Law and Safety)
The positions of scholars on the concept of “judicial decision quality” have been examined. Criteria for a high-quality judicial decision include justice, timeliness, justification, clarity, clear language, and an accessible style. The researchers also distinguish between objective (legal training, legal experience, qualification requirements for judicial candidates, opportunities for practicing judges to improve their skills, mechanisms for monitoring the work of judges, unrestricted public access to judicial decisions, the role of legal science in analysing judicial decisions) and subjective (the judge’s personality, salary, social guarantees, working conditions and ability to organise their work) factors that affect the quality of a judicial decision. The summaries of judicial practice and analytical work on the application of the Supreme Court’s legislation focus on the following requirements for the quality of drafting and execution of court decisions in cases on administrative offences: execution of a judicial decision with strict compliance by the court with the requirements established by law to its form and content, compliance with the legislation on the language of legal proceedings.